Sustainability awareness in society and its impact on the level of responsible business adoption in the business sector of Dubai - Abubaker Mousa Eltoum; Aminurraasyid Yatiban; Rusdi Omar; Rabiul Islam (Problems and Perspectives in Management, 2022)
The private sector is assisting in sustainable development because of the enormous development and rise in commercial and industrial revolutions. However, corporate social responsibility is declining despite this development for several reasons. Among others, they include a lack of belief on the part of owners or boards of directors in the sustainability idea and the prohibitively expensive nature of some technologies. This study aims to examine how community members’ awareness relates to the amount of commitment of businesses in Dubai. In order to investigate the association between two variables, this study used a mixed methods approach that included both interviews and a general questionnaire with several questions. A sample of 314 members of the Dubai community was selected via an electronic platform to collect the data. Descriptive analysis, regression analysis, and pertinent correlations were used to process the data. The findings of this study were encouraging regarding the strength of the link between a person’s social consciousness and their level of commitment to businesses and organizations operating in the exact United Arab Emirates community. Further studies can investigate additional influential factors. The conclusions of this paper may serve as valuable tools for pressuring businesses to increase their effectiveness and efficiency to forge a genuine societal commitment to sustainability. AcknowledgmentFinancial assistance provided by the RIMC (14802) of University Utara Malaysia is gratefully acknowledged.